Criminal punishment and its goals - Bizhanova А.Р.; Osmanova Г.Ж.; Turlykhanova Қ. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2022)
For many years both practitioners of criminal justice bodies and the penitentiary system, and scientists but also of society have been focused on the issues of criminal punishment. Punishment is one of the leading instruments of the state criminal policy, which largely ensures the fulfillment of the tasks assigned to the criminal legislation. Criminal responsibility is carried out with the help of punishment. The effectiveness and significance of the institution of punishment lie in the fact that it allows you to appoint a fair punishment that corresponds to the personality of the perpetrator, and the public danger of his actions. Only in this case, criminal punishment is recognized as a legal measure of coercion. In fact, the widespread trend in society of the use of criminal punishment in practice for intimidation causes many alarms. The author of the article considers some issues of the criminal punishment system proceeding from the purpose of punishment.